Kidney transplantation in an adult patient with VACTERL association. (23rd June 2015) - Cimen, Sertac; Nantais, Jordan; Guler, Sanem; Lawen, Joseph
Abstract : The vertebral, anal, cardiac, tracheoesophageal, renal, and limb birth defects (VACTERL) association is a rare, non-random constellation of congenital abnormalities among which urinary tract anomalies can be included. In the presence of these anomalies, patients are suspected to have a higher rate of renal failure than average. We report a case of a 22-year-old woman with VACTERL association and consequent end stage renal failure. A live-related kidney transplant was carried out successfully and the postoperative course was uncomplicated. The patient had immediate graft function. Risk factors that may complicate kidney transplant surgery in this patient population as well as considerations relevant to peritransplant management are discussed.